Postprocessing of CL Data in CAD/CAM system Edgecam using the Constructor of postprocessors - Čuboňová, Nadežda (Manufacturing Technology Journal, 2013)
Introduction into problems - the present CAD/CAM systems integrate part modelling and engineering design, proposal of technological documentation in the form of NC programs and operational management of production within a one computer system. Their utilization allows the programmer to create machining technology, to define the tool paths and to generate NC programs for very complex shape parts [7]. Final product of CAM system is CL Data files, which include all the steps of toolpaths and technological process. If we want to connect the information produced by the CAM system with the concrete CNC machine, we need to use NC postprocessor. Generator of postprocessors to help users faster creates the specific postprocessor. Universal postprocessor does not exist. Unfortunately, it is necessary to create and to program it for each machine separately. This paper presents a use of the software tool "Constructor of postprocessors", by the creation of postprocessor in CAD/CAM system Edgecam. Postprocessor was developed for turning machine EMCO Concept Turn 55 with control system SIEMENS 840D at the Department of Automation and Production Systems (DAPS) Faculty of Mechanical Engineering.
Keywords: and lower case; normal; justified into block